Two Related Kinesins, klp5(+) and klp6(+), Foster Microtubule Disassembly and Are Required for Meiosis in Fission Yeast - West, Robert R. (The American Society for Cell Biology, 2001)
The kinesin superfamily of microtubule motor proteins is important in many cellular processes, including mitosis and meiosis, vesicle transport, and the establishment and maintenance of cell polarity. We have characterized two related kinesins in fission yeast, klp5(+) and klp6(+), that are amino-terminal motors of the KIP3 subfamily. Analysis of null mutants demonstrates that neither klp5(+) nor klp6(+), individually or together, is essential for vegetative growth, although these mutants have altered microtubule behavior. klp5Δ and klp6Δ are resistant to high concentrations of the microtubule poison thiabendazole and have abnormally long cytoplasmic microtubules that can curl around the ends of the cell. This phenotype is greatly enhanced in the cell cycle mutant cdc25–22, leading to a bent, asymmetric cell morphology as cells elongate during cell cycle arrest. Klp5p-GFP and Klp6p-GFP both localize to cytoplasmic microtubules throughout the cell cycle and to spindles in mitosis, but their localizations are not interdependent. During the meiotic phase of the life cycle, both of these kinesins are essential. Spore viability is low in homozygous crosses of either null mutant. Heterozygous crosses of klp5Δ with klp6Δ have an intermediate viability, suggesting cooperation between these proteins in meiosis.